Description of the experience of a clinical ethics consultation service from 2019 to 2021 - López-Urrutia, E.; Sancha, A.; Useros, D.; Galván-Román, J.M.; García-Sanz, Í.; Casals, F.; Fernández-Bueno, J.; Real de Asúa, D. (Revista clínica espanõla (English edition), 2022)
Clinical ethics consultation services (CEC) are useful model for ethical counselling, albeit with scarce implementation in European countries. This article shares the experience of one of the first ethics consultation services in Spain. This work is a retrospective, observational study of all consultations received by the CEC service at La Princesa University Hospital (Madrid, Spain) from September 1, 2019 to August 31, 2021. The demographic, logistic, and ethical variables of the cases were analyzed. A total of 63 cases were analyzed in which a total of 124 ethical conflicts were identified. Forty-one percent of the cases (n = 26) were emergency consultations and 38% (n = 24) were preferential inquiries. An initial evaluation was performed with 24 h in 50 cases (79%). The department that consulted most often was the Intensive Care Unit (9; 14%). The preferred contact methods were via pager (36; 57%), the electronic medical record system (13; 21%), or direct conversations with consulting team (7; 11%). The most common ethical conflicts were those related to the adequacy of treatment measures (24; 19%), refusal of treatment (19; 15%), communication with the patient or his/her family (29; 23%), or the patient's capacity (13; 11%). CEC services provide quick, efficient assistance for resolving ethical problems in daily practice. Their implementation in Spain is feasible. La consultoría en ética clínica (CEC) es un modelo útil de asesoría ética, pero con escasa implantación en Europa. En el presente artículo se comparte la experiencia de uno de los primeros servicios de consultoría ética en España. Estudio observacional retrospectivo de todas las consultas recibidas por el servicio de CEC del Hospital Universitario de La Princesa (Madrid, España) entre el 1 de septiembre de 2019 y el 31 de agosto de 2021. Se analizaron variables demográficas, logísticas y éticas de los casos. Se analizaron 63 casos, en los que se identificaron un total de 124 conflictos éticos. El 41% (n = 26) de las consultas eran de carácter urgente y el 38% (n = 24), preferentes. La evaluación inicial se realizó en menos de 24 horas en 50 casos (79%). El servicio que consultó con mayor frecuencia fue Medicina Intensiva (9; 14%). Los medios de contacto preferidos fueron el busca (36; 57%), el sistema electrónico de historia clínica (13; 21%) o la conversación directa con el equipo consultor (7; 11%). Los problemas éticos más comunes estaban relacionados con la adecuación de medidas terapéuticas (24; 19%), el rechazo del tratamiento (19; 15%), la comunicación con el paciente o su familia (29; 23%) o la competencia del paciente (13; 11%). Los servicios de CEC proporcionan una asistencia rápida y eficiente para la resolución de problemas éticos en la práctica habitual. Su implementación en España es factible.